Effect of custom-made and prefabricated insoles on plantar loading parameters during running with and without fatigue - Lucas-Cuevas, A. G.; Pérez-Soriano, P.; Llana-Belloch, S.; Macián-Romero, C.; Sánchez-Zuriaga, D. (Journal of Sports Sciences, 2015)
Controversy exists whether custom-made insoles are more effective in reducing plantar loading compared to prefabricated insoles. Forty recreational athletes ran using custom-made, prefabricated, and the original insoles of their running shoes, at rest and after a fatigue run. Contact time, stride rate, and plantar loading parameters were measured. Neither the insole conditions nor the fatigue state modified contact time and stride rate. Addressing prevention of running injuries, post-fatigue loading values are of great interest. Custom-made insoles reduced the post-fatigue loading under the hallux (92 vs. 130 kPa, P < 0.05), medial midfoot (70 vs. 105 kPa, P < 0.01), and lateral midfoot (62 vs 96 kPa, P < 0.01). Prefabricated insoles provoked reductions in post-fatigue loading under the toes (120 vs. 175 kPa, P < 0.05), medial midfoot (71 vs. 105 kPa, P < 0.01), and lateral midfoot (68 vs. 96 kPa, P < 0.01). Regarding both study insoles, custom-made insoles reduced by 31% and 54% plantar loading under the medial and lateral heel compared to the prefabricated insoles. Finally, fatigue state did not influence plantar loading regardless the insole condition. In long-distance races, even a slight reduction in plantar loading at each foot strike may suppose a significant decrease in the overall stress experienced by the foot, and therefore the use of insoles may be an important protective mechanism for plantar overloading.